2022
DOI: 10.20892/j.issn.2095-3941.2021.0388
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of anti-EGFR monoclonal antibody (SCT200) as second-line therapy in advanced esophageal squamous cell carcinoma

Abstract: Objective: The mainstay treatment of esophageal squamous cell carcinoma (ESCC) involves chemotherapy and immunotherapy.However, alternative therapies are required for patients who are refractory or intolerant to existing therapies. Methods: In this single-arm, multicenter, open-label phase Ib study, 30 patients received an intravenous infusion of SCT200, an antiepidermalgrowth factor receptor (EGFR) monoclonal antibody, 6.0 mg/kg once a week for 6 weeks, followed by 8.0 mg/kg once every2 weeks until disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“… 19 , 24 Several previous trials have tried to target EGFR in unselected patient populations and found low response rates. 18 , 19 , 21 , 25 Therefore, the objective response rate and the median PFS recorded in the present study are promising compared with those in other trials involving unselected advanced ESCC patients. However, more than 60% of the metastatic ESCC patients with EGFR overexpression were still nonresponsive, suggesting that there are other underlying mechanisms in addition to EGFR itself.…”
Section: Discussionsupporting
confidence: 58%
“… 19 , 24 Several previous trials have tried to target EGFR in unselected patient populations and found low response rates. 18 , 19 , 21 , 25 Therefore, the objective response rate and the median PFS recorded in the present study are promising compared with those in other trials involving unselected advanced ESCC patients. However, more than 60% of the metastatic ESCC patients with EGFR overexpression were still nonresponsive, suggesting that there are other underlying mechanisms in addition to EGFR itself.…”
Section: Discussionsupporting
confidence: 58%
“…It is clear that 3D organoid models are an ideal platform for examining host-pathogen interactions in the co-culture of the microbiome and esophageal tissue. In addition, the escalating adoption of target therapies in EC has led to accumulating evidence suggesting the potential involvement of esophageal microbiota in modulating the patient response to these treatments 72,73 , thus presenting a significant focus of research in this field.…”
Section: Discussionmentioning
confidence: 99%